2023
DOI: 10.1113/jp283566
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem astrocytes control homeostatic regulation of caloric intake

Abstract: support-information-section).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 75 publications
(126 reference statements)
3
9
0
Order By: Relevance
“…However, there is strong precedence in the literature, including from data in rodent studies examining cholecystokinin (CCK 58 ), prolactin‐releasing peptide (PrRP 59 ) and glucagon‐like peptide‐1 (GLP‐1 60,61 ) signalling, indicating that aversion per se is not necessarily non‐physiological as satiety and nausea/malaise are likely on the same physiological continuum. A recent study by Clyburn and colleagues showed that chemogenetic (GFAP‐hM4DGi) or pharmacological (fluoroacetate) mediated inhibition of astrocytes in the rat dorsal DMV prolongs high‐fat diet induced hyperphagia during the initial homeostatic adjustment to the diet by modulating glutamatergic signalling, resulting in alterations in gastric emptying 62 . While this study focuses on inhibition of DMV astrocyte activity, it supports the notion that specific modulation of these cells in the DVC is sufficient to physiologically impact feeding.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, there is strong precedence in the literature, including from data in rodent studies examining cholecystokinin (CCK 58 ), prolactin‐releasing peptide (PrRP 59 ) and glucagon‐like peptide‐1 (GLP‐1 60,61 ) signalling, indicating that aversion per se is not necessarily non‐physiological as satiety and nausea/malaise are likely on the same physiological continuum. A recent study by Clyburn and colleagues showed that chemogenetic (GFAP‐hM4DGi) or pharmacological (fluoroacetate) mediated inhibition of astrocytes in the rat dorsal DMV prolongs high‐fat diet induced hyperphagia during the initial homeostatic adjustment to the diet by modulating glutamatergic signalling, resulting in alterations in gastric emptying 62 . While this study focuses on inhibition of DMV astrocyte activity, it supports the notion that specific modulation of these cells in the DVC is sufficient to physiologically impact feeding.…”
Section: Discussionsupporting
confidence: 74%
“…A recent study by Clyburn and colleagues showed that chemogenetic (GFAP-hM4DGi) or pharmacological (fluoroacetate) mediated inhibition of astrocytes in the rat dorsal DMV prolongs high-fat diet induced hyperphagia during the initial homeostatic adjustment to the diet by modulating glutamatergic signalling, resulting in alterations in gastric emptying. 62 While this study focuses on inhibition of DMV astrocyte activity, it supports the notion that specific modulation of these cells in the DVC is sufficient to physiologically impact feeding. In agreement with our data, they observed that in control viral vector injected rats CNO treatment (either 1 mg/kg or 3 mg/kg i.p.)…”
Section: Chemogenetic Activation Of Dvc Astrocytes Suppressed Food In...supporting
confidence: 71%
“…Below we discuss the evidence supporting these multifaceted effects of hypothalamic astrocytes influencing metabolic function. While this review focuses on metabolic circuits in the hypothalamus, it is important to note important work indicating that astrocytes influence neuronal activity in extrahypothalamic energy balance centers including the dorsal vagal complex (Clyburn et al, 2023; Cui et al, 2022; Reiner et al, 2016; Troadec et al, 2022).…”
Section: Astrocytes and The Regulation Of Synaptic Plasticity And Ene...mentioning
confidence: 99%
“…This study advances our understanding of how brainstem astrocytes mediate early physiological adaptations to a HFD challenge (Clyburn et al, 2023), with many interesting angles still to pursue. This study focuses on changes in NTS→DMV→gastric neuron circuits, but as significant gastric distention occurs during the hyperphagia immediately following introduction of a HFD, it would be fascinating to examine changes at the vagal-NTS synapse in this paradigm.…”
mentioning
confidence: 94%
“…Understanding the physiological mechanisms underlying satiety may aid development of new therapeutic approaches for disordered eating, particularly in relation to consumption of calorie‐dense foods implicated in the development of obesity. Focusing on a class of cells in the central nervous system called astrocytes, a new comprehensive study by Clyburn and colleagues provides mechanistic insights into the early‐stage molecular and cellular adaptations within the DVC following consumption of a calorie‐rich refined high‐fat diet (HFD) (Clyburn et al., 2023).…”
mentioning
confidence: 99%